Start codon targeted (SCoT) polymorphism reveals genetic diversity of Manilkara in Thailand - Ongkarn Vanijajiva (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Vanijajiva O. 2020. Start codon targeted (SCoT) polymorphism reveals genetic diversity of Manilkara in Thailand. Biodiversitas 21: 666-673. Manilkara consists of four species, namely, Manilkara hexandra, M. kauki, M. littoralis, and M. zapota in Thailand. Particularly, M. zapota (sapodilla), commonly known as Lamut in Thailand, is one of commercially notable edible fruits continues to be a highly valued tree and the fruits are a source of food and income. The objective of this research was to determine the diversity and relationship of Manilkara accessions derived from districts in Thailand based on DNA profiles. Genetic diversity and relationship of all accessions were investigated using Start Codon Targeted (SCoT) marker analysis. Of 30 SCoT primers screened, 27 SCoT primers were identified to be polymorphism. A total of 176 DNA bands with size varied from 120 bp to 1200 bp were amplified, and 101 (57.38%) of them were polymorphic. Based on similarity coefficients, total of 36 accessions were clustered into two groups. The cluster of polymorphism generated by SCoT was associated with their locality and morphological characters. Therefore, the present data provide high-valued information for the management of germplasm, genetic improvement, and conservation of the genetic resources of Manilkara accessions.